Rethinking sand as earth material for a sustainable construction in Egypt - Khater, Dina (Frontiers in Built Environment, 2025)
This research investigates the feasibility of using desert sand as a sustainable substitute for traditional construction materials in Egypt. Utilizing local sand resources in Egypt’s extensive desert landscape could substantially decrease dependence on energy-intensive materials like Portland cement and clay bricks, thereby reducing environmental impact and promoting decarbonization initiatives. This research takes a hierarchical approach to analyzing the geological distribution of distinct Egyptian sand kinds, assessing important national initiatives and legislation, in addition to laboratory findings and concluded mechanical qualities in recent publications. It exposes flaws in Egyptian adopted decarbonization and sustainability programs in concrete and masonry industries. It also investigates construction techniques, including autoclaved aerated concrete (AAC) blocks, which provide environmental and economic advantages compared to traditional clay bricks. Therefore, optimizing the use of sand in the concrete and masonry industries is very suitable for Egypt’s urban growth, as it will enhance decarbonization initiatives, improve thermal insulation, and decrease energy consumption. In accordance to this, the study highlights the necessity for additional experimental validation to incorporate sand-based materials into Egypt’s construction sector, which needs to be supported by policy interventions to standardize and generalize sand-based materials. It concludes with an indicative approach for the integration of the abundant desert sand into the production of Portland Pozzolana Cement (PPC) and the enforcement of AAC block usage for modular based construction through national standards and supply chain optimization.